Intimate partner violence: psycho-physio-pathological sequelae for defining a holistic enriched treatment - Cesari, Valentina; Vallefuoco, Alessandra; Agrimi, Jacopo; Gemignani, Angelo; Paolocci, Nazareno; Menicucci, Danilo (Frontiers in Behavioral Neuroscience, 2022)
Intimate partner violence (IPV) is a health priority, which worldwide, mainly affects women. The consequences of IPV include several psychophysiological effects. These range from altered levels of hormones and neurotrophins to difficulties in emotion regulation and cognitive impairment. Mounting evidence from preclinical studies has shown that environmental enrichment, a form of sensory-motor, cognitive, and social stimulation, can induce a wide range of neuroplastic processes in the brain which consistently improve recovery from a wide variety of somatic and psychiatric diseases. To support IPV survivors, it is essential to ensure a safe housing environment, which can serve as a foundation for environmental enrichment-based interventions. However, some concerns have been raised when supportive housing interventions focus on the economic aspects of survivors’ lives instead of the emotional ones. We thus propose a holistic intervention in which supportive housing is integrated with evidenced-based psychotherapies which could constitute an enriched therapeutic approach for IPV survivors.